Improving Non-wheat Flour Quality As a Form of Local Food Conservation - Soesilowati, Etty; Kariada, Nana; Paramita , Octavianti (KnE Social Sciences, 2019)
The growth rate of Indonesian population increases the community’s dependence on wheat ﬂour which is wholly made from imported wheat. Local carbohydrate sources that can function strategically as food reserves are Indonesian traditional tubers and roots.Tubersandrootsalsocontainsomebioactivecompoundsthathavephysiological effects as antioxidants. The bioactive compounds found in these inferior local tubers are dioscorin, diosgenin, and phenol. These three types of bioactive compounds have been shown to have the ability to ward off free radicals. This study aims to developtuberproductsandincreaseaddedvaluethroughtheutilizationofappropriate technology and diversiﬁcation of processed products. The study used sixteen types of traditional Indonesian tubers. The method used is to reduce the size of the tubers usingcrystallizationmethodandutilizetheblowersystemtocreatethewindfordrying system. The blowing facilitates the process of reducing the water content to improve the durability of the ﬂour. The research applied the mixed method approach. The study was carried out in the laboratory. Data were analyzed using proximate analysis to determine moisture content, ash content, carbohydrate content, protein content and fat content. The results showed that the chemical content of Suweg ﬂour with pregelatinization method at 70 ∘C for 60 min had the highest water, ash, and ﬁber content at 5.79%, 2.49%, and 43.73%, respectively; while the highest carbohydrate content obtained by heating for 10 minutes at 25.80%. In conclusion, traditional tuber ﬂours are sufﬁcient for the use of raw materials for the food industry. Keywords: traditional Indonesian tubers, non-wheat flours, local food